Expression and Endocytosis of Lysosomal Aspartylglucosaminidase in Mouse Primary Neurons - Kyttälä, Aija (J Neurosci, 1998)
Aspartylglucosaminuria (AGU) is a neurodegenerative lysosomal storage disease that is caused by mutations in the gene encoding for a soluble hydrolase, aspartylglucosaminidase (AGA). In this study, we have used our recently developed mouse model for AGU and analyzed processing, intracellular localization, and endocytosis of recombinant AGA in telencephalic AGU mouse neurons in vitro. The processing steps of AGA were found to be similar to the peripheral cells, but both the accumulation of the inactive precursor molecule and delayed lysosomal processing of the enzyme were detected. AGA was distributed to the cell soma and neuronal processes but was not found in the nerve terminals. Endocytotic capability of cultured telencephalic neurons was comparable to that of fibroblasts, and endocytosis of AGA was blocked by free mannose-6-phosphate (M6P), indicating that uptake of the enzyme was mediated by M6P receptors (M6PRs). Uptake of extracellular AGA was also studied in the tumor-derived cell lines rat pheochromocytoma (PC12) and mouse neuroblastoma cells (N18), which both endocytosed AGA poorly as compared with cultured primary neurons. Expression of cation-independent M6PRs (CI-M6PRs) in different cell lines correlated well with the endocytotic capability of these cells. Although a punctate expression pattern of CI-M6PRs was found in fibroblasts and cultured primary neurons, the expression was beyond the detection limit in PC12 and N18 cells. This indicates that PC12 and N18 are not feasible cell lines to describe neuronal uptake of mannose-6-phosphate-tagged proteins. This in vitro data will form an important basis for the brain-targeted therapy of AGU.